Вплив параметрів на розв'язки диференціального рівняння четвертого порядку - Гречка, Яна Олексіївна; Hrechka, Yana (Харків : Харківський національний університет імені В.Н. Каразіна, 2024)
У цій роботі досліджується вплив параметрів на розв’язки диференціального рівняння четвертого порядку. Отримано аналоги функцій sin і cos для диференціального рівняння четвертого порядку з подальшим детальним розглядом їх властивостей. Крім того, досліджується крайова задача з параметрами, яка згодом зводиться до системи інтегральних рівнянь. Шляхом аналізу цієї системи інтегральних рівнянь для неї отримано необхідні умови розв’язності. Для ілюстрації теоретичних результатів наведено декілька прикладів.

In the paper, the influence of parameters on the solutions to a fourth-order differential equation is studied. Analogues of the functions sin and cos for the fourth-order differential equation were obtained, followed by a detailed investigation of their properties. Furthermore, a boundary-value problem with parameters is studied, which is subsequently reduced into a system of integral equations. By analysing this system of integral equations, necessary conditions for its solvability are obtained. To illustrate the theoretical results, several examples are provided.
The influence of parameters on the solutions to a fourth-order differential equation
Keywords: MATHEMATICS::Applied mathematics; лінійне диференціальне рівняння; фундаментальна система розв’язків; крайова задача; linear differential equation; fundamental set of solutions; boundary-value problem